Identification and characterization of a K88- and CS31A-like operon of a rabbit enteropathogenic Escherichia coli strain which encodes fimbriae involved in the colonization of rabbit intestine. - Adams, L M (1997)
Initiation of attaching-effacing lesions, which characterize infections with rabbit enteropathogenic Escherichia coli (REPEC), requires bacteria to adhere to the intestinal epithelium. This adherence is reflected in vitro by the affinity of these E. coli strains for various types of eukaryotic cells. TnphoA mutants of REPEC 83/39 (O15:H-) which had lost the ability to adhere to HEp-2 epithelial cells, guinea pig ileal brush borders, and mouse erythrocytes were generated. DNA sequencing of the region surrounding the inactivating transposon insertions within a 95-kb plasmid, designated pRAP for REPEC adherence plasmid, revealed extensive homology between that region and the structural genes of enterotoxigenic E. coli operons encoding the K88 and CS31A fimbrial adhesins and the genes for the afr2 adhesin from REPEC B10 (O103:H2). Seven genes of the ral operon (for REPEC adherence locus), including three putative minor fimbrial subunit genes (ralC, ralF, and ralH), a major fimbrial subunit gene (ralG), a gene of unknown function (ralI), and genes for two fimbrial subunit chaperones (ralD and ralE), were sequenced. When inoculated perorally into weanling rabbits, a mutant with a TnphoA insertion in the ralE gene showed a 10-fold reduction in colonizing ability, with only 1 of 10 rabbits excreting bacteria compared to all 5 of those infected with the wild-type parent strain (P = 0.002). The severity of the diarrheal illness caused by the mutant strain was also reduced. Western blotting of surface protein extracts of strain 83/39 with hyperimmune anti-83/39 antiserum, adsorbed with the ralE mutant, revealed a 32-kDa protein which was absent from protein extracts of two nonadherent mutants. The adsorbed antiserum also bound to the surface of strain 83/39 but not to nonadherent mutants, as detected by immunogold labeling. These results indicate that the ral operon of REPEC 83/39 contains genes necessary for the biosynthesis of fine fimbriae which are responsible for in vitro adherence of the bacteria and play a role in their colonization of, and hence virulence for, rabbits. The putative major fimbrial subunit is a protein with an observed molecular size of approximately 32 kDa which, when assembled, appears to form a capsule of fimbriae surrounding the bacterium similar to that described for CS31A.